The tax morale of individual taxpayers in Indonesia - Parlaungan, Gorga (Curtin University, 2017)
This research investigates the tax morale of individual taxpayers in Indonesia, employing a mixed methodology approach, utilising survey and interviews as the methods in obtaining the data. The results show individual taxpayers in Indonesia have a high level of tax morale, where perceptions of the legal system and sentiment towards tax are statistically significant factors in influencing the level of tax morale. Age, education level, and financial condition are also found to affect tax morale.